Three new species of the subgenus Unionicola Haldeman, 1842 (Acari, Hydrachnidia, Unionicolidae) from Guizhou, China - Ding, Zhuhui; Jin, Daochao; Guo, Jianjun; Yi, Tianci (Zootaxa, 2019)
By investigating watermite collections from Guizhou province, China in 2006, three new Unionicola species are described: Unionicola (Unionicola) maolanensis sp. nov., Unionicola (Unionicola) xishuiensis sp. nov. and Unionicola (Unionicola) suiyangensis sp. nov.. A key is presented for the hitherto known five Chinese Unionicola species of the subgenus based on males and females.